The geographical environment and the impact of humanity on it - Dilshoda Inomjonova Azamjon qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the concept of geographical environment in the early stages of society, the geographical environment and the phenomena that affect it and the impact of humans on nature, how human beings make changes to nature.